Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Chemical constituents from Micromeria biflora and their chemotaxonomic significance - Chen Peng; Xing-Li Zhang; Deng-Li Xiong; Fei-Yan Zhao; Kun Xie; Hong-Ping He; Ming-Ming Li (Biochemical Systematics and Ecology, 2026)

Chenietains A-G, undescribed phenylpropanoid-related compounds from Cheniella touranensis and their cytotoxic potential in vitro - Xing-Ping Zhang; Yun Wang; Jia-Le Wang; Wu-Yan Chen; Wen-Jie Ma; Yan-Heng Zhou; Ming-Ming Li; Kou Wang (Phytochemistry, 2026)

Orbitally driven ammonium upwelling fueled primary productivity during the peak Cambrian Explosion - Guangming Meng; Haifeng Gai; Chengang Lu; Yanming Zhao; Yineng Tan; Yang Liu; Yue Feng; Gang Li; Xing Wang; Wei Liu; Yijie Xing; Ping Gao; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Shortened sludge retention time orchestrates the synergistic integration of shortcut nitrogen elimination and enhanced phosphorus removal in an A2O process integrating return sludge side-stream fermentation - Yawen Xing; Feiyi Yuan; Jiaxuan Huang; Xuyang Chen; Qian Ping; Lin Wang; Yongmei Li (Journal of Water Process Engineering, 2026)

Toward understanding tidal flat regime shifts: Contrasting hydro-sediment dynamics revealed by paired observations of two tidal flats - Shibing Zhu; Ya Ping Wang; Yuan Li; Qingguang Zhu; Fei Xing; Mingliang Li; Chao Gao; Shucun Sun (Journal of Hydrology, 2026)

Rare earth elements as emerging contaminants: Multi-source release, geochemical tracing, and implications for environmental monitoring and management - Yong-He Han; Ming-Zhu Zou; Dong-Xing Guan; Yi-Xi Li; Ping Xiang; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Environmental Management, 2026)

Water vapor adsorption mechanisms of marine overmature kerogen during graphitization: Systematic analysis based on chemical structure, surface wettability and pore structure - Yijie Xing; Yihao Xing; Guangming Meng; Ping Gao; Yanming Zhao; Wei Liu; Jinku Li; Xianming Xiao (International Journal of Coal Geology, 2026)

Soil reinforcement by Robinia pseudoacacia roots and its stabilization mechanism for shallow root-soil composite slopes - Xing Chen; Yanjun Shen; Ping Ni; Zijian Li; Jinyu Zhu; Yibing Ning; Haitao Wang (Bulletin of Engineering Geology and the Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Acute topical menthol application and exercise performance: A systematic review and meta-analysis of perceptual and physiological responses - Yong Wang; Xiaohan Fan; Hansen Li; Xing Zhang; Mingyue Yin; Kai Xu; Yuming Zhong; Yilin Zhang; Juan Cui; Tianyu Song; Ping Liu; Hengzhi Deng (Journal of Thermal Biology, 2026)

MXene-enhanced self-healing nanocomposite hydrogels with multiple-dynamic-bond crosslinking for motion sensing and information transmission - Ze-Hua Hou; Huan-Jie Che; Zi-Han Jiang; Xing Wu; Jin-Ping Yuan; Jing Li; Jian-Bo Qu (Chemical Engineering Journal, 2026)

Stable isotope labeling LC–MS for profiling the amine submetabolome in a D-lactate treated cell model - Yue-Qiang Chen; Xiao-Xia Dong; Li Liu; Xiu-Ping Chen; Chen-Guo Feng; Li-Xing Zhan; Yue Su; Fang Zhang; Yin-Long Guo (Analytica Chimica Acta, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Unravelling flavor formation in Chinese steamed bread made with fermented glutinous rice wine dough: insights from microbial succession, metabolomics, and volatile profiling - Jia-Xuan Li; Feng-Ping Qin; Meng-Ting Chen; Yu-Yu Liu; Xiao-Na Guo; Ke-Xue Zhu; Fei Gao; Jun-Jie Xing (Food Research International, 2026)

Market mechanism design and trading decision model incorporating renewable energy alliances for the future electricity capacity market of China - Ying-zhu Han; Xing-ping Zhang; Li Liu; Jia-lin Li; Qin-liang Tan; Yuan-fei Li; Yi Du (Energy Policy, 2026)

Anemoside B4 inhibits mitochondrial dysfunction-related mitophagy in asthma by regulating KAT2B/IRF3 axis - Hao Tang; Ping Li; Mingxia Shang; Zhiping Zhou; Xing Yang; Bin Liu (Molecular and Cellular Biochemistry, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Rhizosphere metabolic responses to soil acidification and their implications for nutrient uptake in eggplant - Tianqi Wang; Muhammad Awais; Xiaoyang Yu; Baiyi Bai; Zhen Wang; Ruirui Zhang; Lijie Yu; Dan Zhao; Xing Li; Ping Zhang; Roland Bol; Lijuan Yang (Rhizosphere, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Apparent resistivity evaluation method of slurry diffusion-solidification and grouting effect of water-bearing fractured rock mass - Hao Xu; Zhen-zhong Xing; Sheng-quan He; Lian-zhi Yang; Yi Zhu; Da-zhao Song; Yu Zhang; Jin-tao Dang; Qiang Liu; Li-ming Qiu; Ping Wang (Journal of Applied Geophysics, 2026)

Graphitization of marine kerogen and its effects on nanopores and adsorption performance - Guangming Meng; Xianming Xiao; Haifeng Gai; Yanming Zhao; Yijie Xing; Kun Zhang; Yu Liu; Qin Zhou; Tengfei Li; Wei Liu; Peng Cheng; Ping Gao (Science China Earth Sciences, 2026)

Osteopontin-driven TGF-β1 signaling via integrin αvβ3-NF-κB axis impairs NK cell function in head and neck squamous cell carcinoma - Zhe Shen; Xin Li; Shi Luo; Yuzhang Gao; Imadoudini Hassimi Safia; Jie Jiang; Xin Qi; Wei Huang; Yalan Liu; Xing Fang; Yaoyun Tang; Ping Wu (Apoptosis, 2026)

A Novel Wave-Absorbing Support System for Mitigating Rock Burst in Deep-Buried Hard Rock Tunnels - Yue-Mao Zhao; Zheng-Chen Ge; Ben-Guo He; Cheng-Xiang Yang; Xing-Long Li; Xiao-Jun Yu; De-Xian Li; Yong-Ping Liu (Rock Mechanics and Rock Engineering, 2026)

First report of mitochondrial genomes in Hydryphantoidea: novel genomes, evolution rate, and gene rearrangement patterns in two water mites (Acari: Hydrachnidia) - Xin-Yao Gu; Ping Li; Hao Zhong; Hai-Tao Li; Jian-Jun Guo; Gang Li; Tian-Xing Jing (Experimental and Applied Acarology, 2026)

Comparative analysis of chemical composition in Zanthoxylum avicennae leaves and branches based on UPLC-Q-Orbitrap HRMS, and evaluation of their antioxidant activities - Liang-Qian Zhang; Yuan Tian; Li-Ping Dai; Xing-Er Ye; Yi-Qin Zheng; Nan-Chen Lai; Wei Dai; Qi Wang (Natural Product Research, 2026)

Sediment transport mechanisms in sediment-starved subaqueous deltas: insights from storm-induced gravity flows - Chunye Hu; Fan Zhang; Jin Li; Xiaolei Liu; Fei Xing; Renzhi Li; Hao Wu; Heyu Yu; Ya Ping Wang (Journal of Hydrology, 2026)

Paleoproterozoic granite chronology, geochemical characterization, and geological significance in the Longdu region of northeastern Zambia - Yu-Xuan Wu; A-Lei Gu; Jun-Ping Ren; Ling-An Bai; Li-Bo Zuo; Hong-Wei Sun; Shi Xing; Zi-Jiang Liu (International Geology Review, 2026)

Research on spontaneous combustion thermal generation and transfer effects of coal–based activated carbon and its precursors - Hui-Fei Lyu; Fu-Xing Shen; Yue Li; Cai-Ping Wang; Jun Deng; Wei-Feng Wang (Process Safety and Environmental Protection, 2026)

The degradation pathway and removal effectiveness of atrazine in a Photocatalysis–Microorganism combined system in coastal wetlands - Yufei Dai; Jing Zhao; Li Lu; Jingyu Zhang; Mengxue Xing; Haoyu Zhang; Xin Luo; Zengyuan Niu; Ping Wang; Keqiang Li (Journal of Environmental Management, 2026)

Rice quality recognition method based on multimodal model - Yuan Zhang; Xiao Xing; Lei Zhu; Xin Li; Xiao Yan Xue; Chong Tao Sun; Chen Hao Duan; Yan Ping Du (Food Control, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

Comprehensive genomic analysis of the maize ACP gene family reveals ZmACP1-mediated salt stress tolerance in Arabidopsis - Yunhao Wu; Junyu Chen; Hanqiu Ge; Xing Rong; Yuchen Wang; Meiwang Zhang; Zhigang Li; Yingrui Xi; Junfeng Tang; Junyi Li; Ping Li; Baohua Wang; et al. (Plant Cell Reports, 2026)

A mixed mushroom poisoning in humans associated with the ingestion of Collybiopsis orientisubnuda - Xiu-Juan Li; Chang Xu; Wen-Hao Zhang; Jing Ma; Han-Chi Lei; Jia Li; Yu-Xian Gao; Xing Xia; Ping Wei; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Nanopore characteristics of lower Cambrian shale based on gas adsorption and multifractal analysis: Implications for gas development and CO2 storage - Wei Liu; Xianming Xiao; Ping Gao; Yanming Zhao; Yijie Xing; Qizhang Fan; Guangming Meng; Jinku Li; Qin Zhou; Tengfei Li; Siyi Liu (Fuel, 2026)

Prenatal organophosphate esters exposure impacts placental structure and inflammatory markers in a trimester-specific manner - Yuan Liu; Ping Lv; Xing Wang; Mengqian Zhang; Yifan Wang; Sheng Wang; Mengjuan Lu; Han Li; Hong Gan; Juan Tong; Hui Gao; Fangbiao Tao (Environmental Research, 2026)

Virgibacillus aidingensis sp. nov., a bacterium isolated from a hypersaline sediment in Xinjiang Province, North-west China - Li Yang; Hua-Wei Huang; Juan Wang; Cui-Ping Miao; Yi-Qing Li; Xiang-Tao Cen; Li-Xing Zhao; Wen-Yong Zhu; Shu-Kun Tang (Antonie van Leeuwenhoek, 2026)

Triterpenoid and trichothecenes from a rhizospheric soil-derived Paramyrothecium sp. KMU22107 - Hong-Tao Li; Xing-Yi Guo; Ya-Ting Shao; Wen-Yu Huang; Cui-Ping Miao; Wei Li (Natural Product Research, 2026)

Challenges and solutions to seismic amplitude pitfalls in dim-spot sandstone reservoirs: A case study from the Shaximiao formation, the Western Sichuan Depression, China - Feng Tan; Ping Yang; Jun-Xing Cao; Le Li; Zhihua Cui; Qian Ma (Journal of Applied Geophysics, 2026)

Nitrate reduction of dissolved organic carbon exported by episodic upwelling: A novel explanation for negative carbon isotope excursions during the Ediacaran–Cambrian transition - Guangming Meng; Haifeng Gai; Yaowen Wu; Ping Gao; Chengang Lu; Qin Zhou; Tengfei Li; Qizhang Fan; Wei Liu; Yanming Zhao; Yijie Xing; Jinku Li; et al. (Global and Planetary Change, 2026)

Maternal linoleic acid intake disrupts early immune-microbiota-fatty acid programming and increases offspring food allergy risk - Tianliang Bai; Chuang Chen; Huming Shao; Fan Yang; Xing Zhang; Ping Tong; Xuanyi Meng; Yong Wu; Hongbing Chen; Xin Li (Food Bioscience, 2026)

Mechanistic insight into curcumin-induced conjugative plasmid transfer acceleration: Role of intracellular arginine uptake - Min-ge Wang; Kai-di Liu; Wen-jie Jin; Run-bo Li; Jun-qi Liu; Liang-xing Fang; Jian Sun; Xiao-ping Liao (Food Microbiology, 2026)

Mapping the spatial variability of hydrogen and oxygen isotopic compositions in Chinese lake water: Patterns and drivers - Hu Liu; Ping Zhang; Huanye Wang; Zhoufeng Wang; Zhonghui Liu; Meng Xing; Zheng Wang; Yixuan Li; Yunning Cao; Xiangzhong Li; Weiguo Liu (Science China Earth Sciences, 2026)

Analysis of clinical characteristics and prognostic factors in AIDS complicated by cryptococcal meningitis - Yanlan Liang; Xiyang Dong; Yong Deng; Zhende Lin; Caixia Zheng; Jiaxuan Li; Yijie Lin; Huatang Zhang; Xing Wang; Wenwu Lin; Wencong Hong; Su Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Phosphorus incorporation drives charge distribution optimization and oxygen deficiency of cobalt‑nickel oxide nanoflakes with enhanced electrochemical performance for supercapacitor - Qinghai Ma; Ping Wang; Gaofeng Li; Fang Cui; Bin Yang; Zhijun Qiao; Dianbo Ruan; Xing Liu; Tieyu Cui (Chemical Engineering Journal, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

Sex- and Age-Specific Inverted U-Shaped Links between Dietary Iron Intake and Serum α‑Klotho in Chinese Adults - Baodi Xing; Jie Yu; Yiwen Liu; Qi Gao; Xinyue Chen; Shuli He; Fan Ping; Lingling Xu; Wei Li; Huabing Zhang; Yuxiu Li (Biological Trace Element Research, 2025)

Machine learning-driven intelligent screening system for synergistic compound reagent in coal slime flotation - Deke Zhang; Ao Li; Jinyong Li; Yangchao Xia; Budeebazar Avid; Lucai Long; Yuan Ping; Yongchao Piao; Yaowen Xing; Xiahui Gui (Minerals Engineering, 2025)

Elucidating flavor compounds in Chinese steamed bread via glutinous rice wine-fermented dough technique: A triangulated analysis combining electronic tongue, SPME-GC-MS, and quantitative descriptive analysis - Jia-Xuan Li; Feng-Ping Qin; Meng-Ting Chen; Yu-Yu Liu; Xiao-Na Guo; Ke-Xue Zhu; Fei Gao; Jun-Jie Xing (Food Bioscience, 2025)

Two pairs of novel isochromanone derivatives with antiadipogenic effects from the cultures of Ganoderma gibbosum - Yu-Jie Li; Xiao-Cui Liu; Yi Luo; Ming-Hua Qiu; Ping Zhao; Xing-Rong Peng (Phytochemistry Letters, 2025)

Efficient room-temperature hydrolytic cleavage of CS2 via Pd-anchored polynitrogen porous polymers - Kai-Wen Jiang; Xing-Yu Chen; Xiao-Li Jiang; Qing-Ya Sun; Yu-Peng Dai; Hui-Zhen He; Ying Zhou; Ping Shang; Xuan-Feng Jiang (Journal of Hazardous Materials, 2025)

Experimental and theoretical calculation study on phosphorus removal by nZVI-loaded biochar/active clay: Synergism of chemical bonding and coordination - Tong Hao; Chen Zhao; Mingyu Shan; Yubo Ding; Kongna Wu; Xing Dai; Juan Li; Ping Zeng (Journal of Environmental Chemical Engineering, 2025)

The synergistic enhancement of adsorption for Pb2+ and organic dyes by a chitosan-based hydrogel as a multipollutant adsorbent - Yun Wang; Li-Ping Fang; Chen-Yang Li; Chang-Jing Cheng; Ting Liang; Xing-Bin Lv; Hai-Rong Yu (Journal of Environmental Chemical Engineering, 2025)

Chemical constituents of Engleromyces sinensis and their chemotaxonomic significance - Xiao-Xue Jiang; Lai-Wei Li; Xing-Ping Zhang; Ke-Pu Huang; Wen-Jie Ma; Li-Ping Tang; Kou Wang (Biochemical Systematics and Ecology, 2025)

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Tongxinluo alleviates myocardial ischemia–reperfusion injury by inhibiting the pyroptosis of endothelial cells via the NLRP3/Caspase-1/GSDMD signaling pathway - Xuan Wu; Yun-long Hou; Tong-xing Wang; Li-ping Chang; Hong-ru Zhou; Ming-ye Wang; Yi-ling Wu (Journal of Molecular Histology, 2025)

Transcriptome profiling of mRNA responding to inflammation in bovine mammary epithelial cells induced by lipopolysaccharide - Jin-peng Wang; Zheng-xing Wang; Bin-wu Bao; Yan-xia Li; Zhuo-ma Luoreng; Xing-ping Wang (Research in Veterinary Science, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Proteomics and metabolomics reveal the role of miR-320b in regulating inflammation of bovine mammary epithelial cells - Li Zhou; Zhuo-Ma Luoreng; Xing-Ping Wang; Ya-Qing Dou; Hui Li (Research in Veterinary Science, 2025)

Isolation of dihydroagarofuran sesquiterpene from the fruits of Tripterygium hypoglaucum and evaluation of their anti-inflammatory activity - Shi-Li Wu; Xing Yang; Wen-Xiu Ning; Gang-Yun Wu; Xin-Yu Dai; Yu Zhang; Duo-Zhi Chen; Xiao Ding; Hong-Ping He; Wei Zhou; Xiao-Jiang Hao (Phytochemistry, 2025)

Denitrification dominates nitrate attenuation and nitrous oxide effluxes under water table fluctuations - Lin Zhang; Helin Wang; Xiaohan Liu; Hongbin Zhan; Uwe Schneidewind; Stefan Krause; Menggui Jin; Xing Liang; Yanfeng Liu; Ping Li (Journal of Hazardous Materials, 2025)

Investigating fracture response characteristics and fractal evolution laws of pre-holed hard rock using infrared radiation: Implications for construction of underground works - Ze-Kun Zhang; Jin-Xing Lai; Zhan-ping Song; Yong-Li Xie; Jun-ling Qiu; Yun Cheng; Le Zhang (Tunnelling and Underground Space Technology, 2025)

Effect of wave height on seismic fragility of subsea tunnels in sandy seabed - Ling-Yu Xu; Ju-Ping Xi; Jia-Wei Jiang; Fei Cai; Yong-Yi Li; Guo-Xing Chen (Ocean Engineering, 2025)

Mechanism study of the effects of astragaloside IV and quercetin on idiopathic pulmonary fibrosis - Ye Luo; Chang-jun Xu; Xing-hui Ai; Yu-ping Li; Xing Zhu; Chang-fu Yang (Journal of Natural Medicines, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Impact of fermentation duration in fermented glutinous rice wine dough procedure on the staling of Chinese steamed bread - Jia-Xuan Shang; Jia-Xuan Li; Feng-Ping Qin; Yi-Peng Bai; Xiao-Na Guo; Ke-Xue Zhu; Jun-Jie Xing (Food Bioscience, 2025)

The transcription factor CsPAT1 from tea plant (Camellia sinensis) is involved in drought tolerance by modulating phenylpropanoid biosynthesis - Jing-Wen Li; Ping Zhou; Zhi-Hang Hu; Ai-Sheng Xiong; Xing-Hui Li; Xuan Chen; Jing Zhuang (Journal of Plant Physiology, 2025)

PdRh bimetallic-loaded α-Fe2O3 nanospindles with Ppb-limit of 3-hydroxy-2-butanone biomarker detection: Particle dimension regulation and oxygen spillover effect - Xing-Yu Wang; Ping-Ping Liu; Hai-Jie Cai; Miao-Miao Li; Chun-Hui Deng; Yong Zhao; Zhao-Huan Zhang; Yong-Heng Zhu (Chemical Engineering Journal, 2025)

Fully recyclable flame-retardant PLA composites with balanced performance based on a phosphorus/nitrogen-containing zwitterion - Qiang Zhang; Xing Cao; Yan-Peng Ni; Li-Ping Zhang; Zhao Ding; Ying-Jun Xu; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Dynamic effects of Aeromonas sobria infection on intestinal morphology, microbiota and goblet cells of rainbow trout (Oncorhynchus mykiss) - Li-Ping Liu; Peng-Tian Kang; Feng-Yuan Ding; Dong-Hong Shao; Bao-Shan Wang; Juan Yang; Wen-Hui Gao; Wang-Dong Zhang; Wen-Hui Wang; Ji-Xing Liu (Aquaculture, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Highly efficient flame-retardant plasticizers for flexible poly(vinyl chloride) via the synergism of integrated isocyanurate, DOPO and poly(ε-caprolactone) - Xing-Ping Zhang; Jing Zhao; Xing-Hao Wang; Yu Chen; Hai-Chao Li; Liang Yang (Chemical Engineering Journal, 2025)

Molecular weight distribution and structure analysis of phlorotannins in Sanhai kelp (Saccharina japonica) and evaluation of their antioxidant activities - Jing Zhang; Long Xing; Wenya Meng; Xiaojie Zhang; Jing Li; Ping Dong (Food Chemistry, 2025)

Defective Zn1-xCuxS nanosheet as efficient and durable cathode catalyst for photo-assisted Li-O2 batteries - Cong-Cong Dang; Yi-Ping Liu; Yu-Xin Huang; Xin-Yi Zhang; Zhen-Yi Gu; Jun-Ming Cao; Jin-Zhi Guo; Li-Ming Gao; Xing-Long Wu; Yi-Chun Liu (Chemical Engineering Journal, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

ADAR1 Promotes NUPR1 A-to-I RNA Editing to Exacerbate Ischemic Brain Injury by Microglia Mediated Neuroinflammation - Guo-Ping Wang; Wen-Juan Li; Ye Li; Ming-Xing Ma; Kai-Kai Guo (NeuroMolecular Medicine, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Molecular fractionation mediates genotoxicity evolution of hydrochar-derived dissolved organic matter at the iron oxyhydroxides-water interface - Yan-Jun Liu; He-Yun Yang; Shu-Xian Gao; Zheng-Hao Li; Yan-Yun Hu; Xing Zheng; Guo-Ping Sheng (Water Research, 2025)

Investigating the application of multiple-stage fermented glutinous rice procedure in dough preparation for Chinese steamed bread - Jia-Xuan Li; Jia-Xuan Shang; Feng-Ping Qin; Xiao-Na Guo; Ke-Xue Zhu; Jun-Jie Xing (Food Bioscience, 2025)

TPT disrupts early embryonic development and glucose metabolism of marine medaka in different salinites - Tengzhou Li; Luoxin Li; Bin Liu; Shaoying Xing; Ling Liu; Ping Li; Zhi-Hua Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Nanoplastic-mineral heteroaggregation under varying degrees of plastic pollution: Implications for antibiotic adsorption in aquatic systems - Xiupei Zhou; Aoze Li; Marko Cerne; Sophie MacRae; Ian Eggleston; Hongtao Qiao; Xiaoyun Li; Guoyong Huang; Ping Wang; Jian Zhao; Baoshan Xing (Chemical Engineering Journal, 2025)

Methane emissions from the riverine sandy wetlands on the Mongolia Plateau - Ang Li; Zun-Lan Luo; Katerina Machacova; Song Zhao; Jin-Chao Feng; Xing-Guo Han; Zhi-Ping Wang (Environmental Monitoring and Assessment, 2024)

Physiological Function Disturbances and Adaptive Responses in Nile Tilapia (Oreochromis niloticus) Under Different Salinity Stresses - Ping Li; Tengzhou Li; Shaoying Xing; Ling Liu; Zhi-Hua Li (Fishes, 2024)
The physiological functions of aquatic organisms are closely linked to changes in environmental salinity. High-salinity environments can disrupt energy metabolism, induce inflammation, and negatively impact normal growth and development. However, aquatic organisms possess self-regulatory mechanisms that can mitigate these impacts to some extent. This study aimed to investigate the adaptive regulatory processes in Nile tilapia (Oreochromis niloticus, Linnaeus, 1758) exposed to high-salinity environments by evaluating metabolic enzyme activities and levels of inflammatory markers. The increased levels of IL-1β and elevated ACP activity suggested that high-salinity conditions (15 and 30 ppt) induced intestinal inflammation. Concurrently, the elevated activities of SOD and GSH, along with decreased SDH activity, pointed to heightened oxidative stress in the brain and a reduced mitochondrial energy supply. Additionally, the adaptive features of intestinal energy metabolism under high-salinity conditions were evident, with adjustments in HK and PK activities mitigating the effects of suppressed PFK activity. Moreover, elevated lipase (LPS) activity in muscle tissue under salinity stress indicated that fat is mobilized to supply energy for muscle activity without affecting muscle protein. In conclusion, salinity stress triggered inflammatory and oxidative stress responses in Nile tilapia, yet the fish exhibited self-regulatory processes in energy metabolism. This study provides a theoretical basis for understanding the adaptive mechanisms of aquatic organisms in stressful environments.

Structurally diverse ent-clerodanoids from the aerial parts of Isodon scoparius - Xue-Chun Jiang; Kun Hu; Xue Bai; Xing-Ren Li; Bing-Chao Yan; Su-Ping Chen; Xiao-Nian Li; Han-Dong Sun; Pema-Tenzin Puno (Phytochemistry, 2024)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Metagenomic analysis unveiled the response of microbial community and antimicrobial resistome in natural water body to duck farm sewage - Chang Fang; Kai-di Liu; Feng-jie Tian; Jin-ying Li; Si-jie Li; Rong-min Zhang; Jian Sun; Liang-xing Fang; Hao Ren; Min-ge Wang; Xiao-ping Liao (Environmental Pollution, 2024)

Acid-assisted pretreatment for sweet elephant grass in choline chloride/glycerol DES: Experimental and mechanism study - Yining Zhang; Weizhen Xie; Weidong Li; Yue Tang; Jiali Wu; Lihui Gan; Ling-Ping Xiao; Xu Zhang; Lu Lin; Xing Tang (Chemical Engineering Journal, 2024)

Exploring the material basis and molecular targets of Changma Xifeng tablet in treating Tourette syndrome: an integrative approach of network pharmacology and miRNA analysis - Jing Peng; Qiaoling Li; Linhui Liu; Ping Gao; Lipeng Xing; Li Chen; Hui Liu; Zhisheng Liu (Metabolic Brain Disease, 2024)

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

Improved recovery of lithium from spent lithium-ion batteries by reduction roasting and NaHCO3 leaching - Wenke Liu; Qingwei Qin; Hailin Zhang; Wei Zhao; Xing Chen; Jiachun Xiong; Yunwu Han; Shili Zheng; Chunguang Zhang; Guangqiang Li; Ping Li (Waste Management, 2024)

Effect of lead exposure on silkworm midgut: Insights into oxidative gene expression, digestive function, and microbial community structure - Yan-Xia Shi; Dan-Dan Bian; Fan-Xing Chen; Ye Jin; Qi Jiang; Qiu-Ning Liu; Bo-Ping Tang; Li-Shang Dai (Process Safety and Environmental Protection, 2024)

Occurrence and maturation transformation of organic and inorganic nitrogen in the Lower Cambrian shelf–slope facies shale: Implications for overmature N2-rich shale reservoirs in Southern China - Guangming Meng; Haifeng Gai; Xiumin Yang; Ping Gao; Qin Zhou; Chengang Lu; Gang Li; Xing Wang; Peng Cheng (Marine and Petroleum Geology, 2024)

Simulating liquefaction-induced resuspension flux in a sediment transport model - Zichen Zhu; Xing Du; Bingchen Liang; Linfeng Wang; Yupeng Song; Ping Li; Yaoshen Fan; Shuhua Bian; Yongzhi Wang; Yongqiang Zhang; Bing Li (Water Research, 2024)

Prevalence and molecular characteristics of intestinal pathogenic Escherichia coli isolated from diarrheal pigs in Southern China - Qian Li; Jing-Jing Dai; Shu-Yi Chen; Ruan-Yang Sun; Dong Wang; Shuan-Cheng Bai; Min-Ge Wang; Jian Sun; Xiao-Ping Liao; Ya-Hong Liu; Liang-Xing Fang (Veterinary Microbiology, 2024)

Sediment dynamic on the tidal flat sheltered by artificial engineering: A case study on eddies - Shaoxin Chen; Haifei Yang; Mingliang Li; Fei Xing; Benwei Shi; Ya Ping Wang (Estuarine, Coastal and Shelf Science, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Recent progress and perspectives on coal dust sources, transport, hazards, and controls in underground mines - Yong Cao; Yang Xiao; Zhen-Ping Wang; Qing-Wei Li; Chi-Min Shu; Xing-Rui Jiang; Shi-Liang Wu (Process Safety and Environmental Protection, 2024)

Unveiling the molecular mechanisms of size-dependent effect of polystyrene micro/nano-plastics on Chlamydomonas reinhardtii through proteomic profiling - Xiaoxue Li; Zheng Chu; Chenran Feng; Ping Song; Tong Yang; Lirun Zhou; Xin Zhao; Xin Chai; Jiale Xing; Sa Chen; Junzhe Zhang; Jigang Wang; et al. (Chemosphere, 2024)

P53 upregulation by USP7-engaging molecular glues - Zhaoyang Li; Ziying Wang; Chao Zhong; Hang Zhang; Rui Liu; Ping An; Zhiqiang Ma; Junmei Lu; Chengfang Pan; Zhaolin Zhang; Zhiyuan Cao; Jianyi Hu; et al. (Science Bulletin, 2024)

Experimental study on the hydrodynamic performance of a side-by-side box-membrane breakwater - Jing-Ping Wu; Chuan-Rui Li; Jing-Jing Qi; Xing-Yu Xu; Jia-Ning Li; Xiu-Xing Zhang; Qing Qin; Zhi-Rong Zhou (Ocean Engineering, 2024)

Optimized dual-gas co-production from hydrate reservoirs with underlying gas through depressurization & well closure cycling: An experimental evaluation - Xian Sun; Xiao-Hui Wang; Peng Xiao; Yi-Fei Sun; Xing-Xun Li; Wei-Xin Pang; Qing-Ping Li; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2024)

Binding properties of chemosensory protein 4 in Riptortus pedestris to aggregation pheromones - Jin-Bu Li; Qiang Liu; Sai Ma; Yue-Ying Wang; Xing-Zhou Liu; Chao-Wei Wang; Da-Jiang Wang; Zhuang-Zhuang Hu; Jia-Wen Gan; Xiu-Yun Zhu; Bao-Ping Li; Mao-Zhu Yin; et al. (Pesticide Biochemistry and Physiology, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Windows of sensitivity for risk of adverse birth outcomes related to gestational PM2.5 exposure: Evidence from a natural experiment - Wei Ni; Yuhan Xing; Guoju Li; Zhanhui Du; Ping Yang; Qinzheng Wang; Xinmeng Yang; Bei Lyu; Hongge Fa; Qiuling Shi; Quansheng Xing (Environmental Pollution, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Seasonal variations and size-dependent distribution of heavy metals in particulate matter in Huangshi: Implications for human health risk assessment - Yuhu Xie; Yao Mao; Ping Zhong; Yong Zhang; Li Zhang; Wei Chen; Chengkai Qu; Xinli Xing; Junji Cao; Jiaquan Zhang (Atmospheric Environment, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Silybin mitigates chronic Avermectin exposure-induced intestinal damage and growth inhibition in carp - Guanglu Wang; Yue Xin; Kaixin Ping; Xuhui Xu; Ying Sun; Xing Li; Xinying Guan; Jingquan Dong (Environmental Toxicology and Pharmacology, 2024)

Pesticide avermectin-induced hepatotoxicity and growth inhibition in carp: Ameliorative capacity and potential mechanisms of quercetin as a dietary additive - Yue Xin; Xueqing Li; Kaixin Ping; Yannan Xiang; Mengxin Li; Xing Li; Haitao Yang; Jingquan Dong (Aquatic Toxicology, 2024)

CsBZR1 Family Transcription Factors in Wild and Cultural Tea Plants and Their Response to Hormone and Abiotic Stress - Jing-Wen Li; Ping Zhou; Ni Yang; Zhi-Hang Hu; Yi Chen; Wei Luo; Jie-Yu Kong; Zhi-Yuan Qin; Xing-Hui Li; Xuan Chen; Jing Zhuang (Journal of Plant Growth Regulation, 2024)

Immunoprotective effect of silybin through blocking p53-driven caspase-9-Apaf-1-Cyt c complex formation and immune dysfunction after difenoconazole exposure in carp spleen - Enzhuang Pan; Yue Xin; Xueqing Li; Kaixin Ping; Xing Li; Ying Sun; Xuhui Xu; Jingquan Dong (Environmental Science and Pollution Research, 2024)

Investigation on the failure mechanism of a tunnel entrance high-steep slope with ultra-large wedge blocks based on discrete element method - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Xiu-yang Liu; Yue-lin Xia; Guan-qi Wang; Xing-dong Ma; Zheng-jun Zhou (Computers and Geotechnics, 2024)

Fabrication of robust mechanical NiCo nanocubes for lithium metal anode with superior high rate performance - Yi-Han Song; Yan-Fei Li; Jian Lin; Guo-Duo Yang; Xing-Long Wu; Jing-Ping Zhang; Hai-Zhu Sun; Liang Zhao (Chemical Engineering Journal, 2024)

Diversified cropping systems with complementary root growth strategies improve crop adaptation to and remediation of hostile soils - Wei-Ping Zhang; Surigaoge Surigaoge; Hao Yang; Rui-Peng Yu; Jin-Pu Wu; Yi Xing; Yinglong Chen; Long Li (Plant and Soil, 2024)

Whole-cell bioreporter application for rapid evaluation of hazardous metal bioavailability and toxicity in bioprocess - Xiaokai Zhang; Yi Zhu; Evrim Elçin; Lizhi He; Boling Li; Mengyuan Jiang; Xing Yang; Xiu-Ping Yan; Xu Zhao; Zhenyu Wang; Fang Wang; Sabry M. Shaheen; et al. (Journal of Hazardous Materials, 2024)

Variable depositional environments and organic matter enrichment of Early Cambrian shales in the Middle Yangtze region, South China - Wei Liu; Ping Gao; Xianming Xiao; Yanming Zhao; Yijie Xing; Jinku Li (Journal of Asian Earth Sciences, 2024)

Exploring the formation and retention of aroma compounds in ready-to-eat roasted pork from four thermal methods: A lipidomics and heat transfer analysis - Huan Liu; Qianli Ma; Jiangtao Xing; Pi Li; Peng Gao; Nazimah Hamid; Zhongshuai Wang; Ping Wang; Hansheng Gong (Food Chemistry, 2024)

Fluid mud induced by periodic tidal advection and fine-grained sediment settling in the Yangtze estuary - Hao Wu; Jieping Tang; Weihua Li; Fei Xing; Haifei Yang; Fan Zhang; Ya Ping Wang (Frontiers in Marine Science, 2023)
This study presents in-situ observations of fluid mud in the Yangtze Estuary via a bottom tripod. Six occurrences of periodic fluid muds (F1-F6) were observed at high slack water, with suspended sediment concentration (SSC) exceeding 10 kg/m 3 . The thickness of the fluid mud varied across the six occurrences, reaching a maximum of 0.32m. Notably, temperature and salinity anomalies were observed within the fluid mud. The formation of fluid mud was found to be influenced by turbulence, with turbulence kinetic energy (TKE) below 5×10 -4 m 2 /s 2 favoring settling as the primary cause of formation. The critical shear stress ( τ cw ) for fluid mud formation was estimated to be approximately 0.09 Pa. The formation of fluid muds during early tidal cycles was attributed to liquefaction and bed erosion resulting from strong waves. However, in most cases, the wave energy was insufficient for erosion, suggesting that advection played a role in sediment supply during the subsequent tide cycles. The increased cross-channel current velocity during flood facilitated the lateral transport of a significant amount of eroded sediment from shallow water into the channel. Due to its short duration, the fluid mud layer was entrained by the current before consolidation. Enhanced turbulence led to the breakdown of fluid mud at the early ebb. The critical τ cw for fluid mud breakdown depended on the density and duration of the fluid mud, with a maximum value of up to 0.70 Pa. The absence of the fluid mud layer during low slack water and neap tide was associated with a reduction in advection and tidal pumping, disrupting the original sediment balance between supply and demand. These data provide valuable insights into the formation and breakdown of fluid mud, contributing to estuarine hydrodynamic modeling studies and enhancing the understanding of estuary dynamics.

Soybean WRINKLED1 protein GmWRI1a promotes flowering under long-day conditions via regulating expressions of flowering-related genes - Zhikun Wang; Siqi Xing; Meng Li; Qingyan Zhang; Qiang Yang; Pengfei Xu; Bo Song; Ping Shang; Mingming Yang; Changhuan Du; Jihan Chen; Shanshan Liu; et al. (Plant Science, 2023)

Relationship of individual and mixed urinary metals exposure with liver function in the China National Human Biomonitoring (CNHBM) of Zhejiang Province - Ping Cheng; Yi Tao; Jinfeng Hu; Hongxin Wang; Ruifang Zhao; Shenghua Mei; Yin Yang; Fugen Ye; Zhijian Chen; Hao Ding; Mingluan Xing; Peiwei Xu; et al. (Chemosphere, 2023)

Lindenane sesquiterpenoid dimers from Chloranthus holostegius with anti-neuroinflammatory activities in BV-2 microglia - Zhao-Chun Zhan; Yi-Ping Xia; Qing Tang; Hui-Hui Zhu; Jing-Yi Du; Jun-Xing Cai; Yan-Jun Chen; Zhong-Nan Wu; Yao-Lan Li; Neng-Hua Chen; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2023)

Understanding the role of lipids in aroma formation of circulating non-fried roasted chicken using UHPLC-HRMS-based lipidomics and heat transfer analysis - Huan Liu; Dengyong Liu; Raheel Suleman; Peng Gao; Pi Li; Jiangtao Xing; Qianli Ma; Nazimah Hamid; Ping Wang; Hansheng Gong (Food Research International, 2023)

Repair of dysfunctional bone marrow endothelial cells alleviates aplastic anemia - Shu-Qian Tang; Tong Xing; Zhong-Shi Lyu; Li-Ping Guo; Mi Liang; Chen-Yuan Li; Yuan-Yuan Zhang; Yu Wang; Lan-Ping Xu; Xiao-Hui Zhang; Xiao-Jun Huang; Yuan Kong (Science China Life Sciences, 2023)

The chemistry and activity-orientedcharacterization of isoflavones difference between roots of Pueraria lobata and P. thomsonii guided by feature-based molecular networking - Ye Zhang; Dong Xu; Xue Xing; Hua Yang; Wen Gao; Ping Li (Food Chemistry, 2023)

Association of urinary bisphenols with thyroid function in the general population: a cross-sectional study of an industrial park in China - Yang Hu; Shiming Lai; Ying Li; Xiaodong Wu; Mingluan Xing; Xueqing Li; Dandan Xu; Yuan Chen; Jie Xiang; Ping Cheng; Xiaofeng Wang; Zhijian Chen; et al. (Environmental Science and Pollution Research, 2023)

Continuous extensional uplift controls the Silurian structural evolution of the Sichuan Basin, southwest China - Gen Li; Zhong-Quan Li; Dian Li; Heng-Lin Liu; Shan Yan; Gui-Ping Su; Xing-Wang Tian (Marine and Petroleum Geology, 2023)

In situ growth of NH2-MIL-101 metal organic frameworks on biochar for glyphosate adsorption - Qi Wang; Kang-Ping Cui; Tong Liu; Chen-Xuan Li; Jun Liu; Dian-Chao Kong; Rohan Weerasooriya; Xing Chen (Chemosphere, 2023)

Face mask derived micro(nano)plastics and organic compounds potentially induce threat to aquatic ecosystem security revealed by toxicogenomics-based assay - Yan-Jun Liu; He-Yun Yang; Yan-Yun Hu; Zheng-Hao Li; Hao Yin; Yun-Tian He; Keng-Qiang Zhong; Li Yuan; Xing Zheng; Guo-Ping Sheng (Water Research, 2023)

Identification of new conserved linear B-cell epitopes in the 3AB and 3C protein of Senecavirus A - Jian Li; Junfang Yan; Yanni Gao; Xing Liu; Haifeng Sun; Juan Bai; Ping Jiang (Veterinary Microbiology, 2023)

Melatonin-induced plant adaptation to cadmium stress involves enhanced phytochelatin synthesis and nutrient homeostasis in Solanum lycopersicum L. - Qufan Xing; Md. Kamrul Hasan; Zhichao Li; Ting Yang; Weiduo Jin; Zhenyu Qi; Ping Yang; Guanghui Wang; Golam Jalal Ahammed; Jie Zhou (Journal of Hazardous Materials, 2023)

Dual-gas co-production behavior for hydrate-bearing coarse sediment with underlying gas via depressurization under constrained conditions - Xian Sun; Xiao-Hui Wang; Peng Xiao; Yi-Fei Sun; Xing-Xun Li; Wei-Xin Pang; Qing-Ping Li; Chang-Yu Sun; Guang-Jin Chen (Gas Science and Engineering, 2023)

The health risk of acetochlor metabolite CMEPA is associated with lipid accumulation induced liver injury - Wei-Guo Wang; Mu-Yao Li; Lin Diao; Cheng Zhang; Li-Ming Tao; Wei-Xing Zhou; Wen-Ping Xu; Yang Zhang (Environmental Pollution, 2023)

Evaluation of Physiological Stress of Grass Carp Chronically Exposed to Enrofloxacin Based on IBR Index - Xu-Qian Cao; Xu Wang; Bin Liu; Shu-Wen He; Zhi-Han Cao; Shao-Ying Xing; Ping Li; Zhi-Hua Li (Water, Air, & Soil Pollution, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

TRIM7 inhibits encephalomyocarditis virus replication by activating interferon-β signaling pathway - Minjing Li; Junfang Yan; Huixin Zhu; Chengyi Guo; Xiaolin Jiang; Yanni Gao; Xing Liu; Ping Jiang; Juan Bai (Veterinary Microbiology, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

RNA-seq reveals the role of miR-223 in alleviating inflammation of bovine mammary epithelial cells - Yan-Xia Li; Peng Jiao; Xing-Ping Wang; Jin-Peng Wang; Fen Feng; Bin-Wu Bao; Yi-Wen Dong; Zhuo-Ma Luoreng; Da-Wei Wei (Research in Veterinary Science, 2023)

Formation and transport of fluid mud triggered by typhoon events in front of the subaqueous Changjiang Delta - Jieping Tang; Hao Wu; Fei Xing; Fan Zhang; Bixuan Tang; Gaocong Li; Ya Ping Wang (Marine Geology, 2023)

Juvenile hormone regulates the photoperiodic plasticity of elytra coloration in the ladybird Harmonia axyridis - Jia‐Xu Li; Zhong Tian; Xing‐Feng Liu; Bei Li; Hao‐Min An; Colin S. Brent; Jia‐Lu Wang; Xiao‐Ping Wang; Wen Liu (Molecular Ecology, 2023)
Many animals, including insects, exhibit plasticity of body colour in response to environmental changes. Varied expression of carotenoids, major cuticle pigments, significantly contributes to body colour flexibility. However, the molecular mechanisms by which environmental cues regulate carotenoid expression remain largely unknown. In this study, we used the ladybird Harmonia axyridis as a model to investigate the photoperiodic‐responsive plasticity of elytra coloration and its endocrine regulation. It was found that H. axyridis females under long‐day conditions develop elytra that are much redder than those under short‐day conditions, resulting from the differential accumulation of carotenoids. Exogenous hormone application and RNAi‐mediated gene knockdown indicate that carotenoid deposition was directed through the juvenile hormone (JH) receptor‐mediated canonical pathway. Moreover, we characterized an SR‐BI/CD36 ( SCRB ) gene SCRB10 as the carotenoid transporter responding to JH signalling and regulating the elytra coloration plasticity. Taken together, we propose that JH signalling transcriptionally regulates the carotenoid transporter gene for the photoperiodic coloration plasticity of elytra in the beetles, which reveals a novel role of the endocrine system in the regulation of carotenoid‐associated animal body coloration under environmental stimuli.

Erosion and accretion of salt marsh in extremely shallow water stages - Dezhi Chen; Jieping Tang; Fei Xing; Jun Cheng; Mingliang Li; Yiyi Zhang; Benwei Shi; Lianqiang Shi; Ya Ping Wang (Frontiers in Marine Science, 2023)
Salt marshes, which commonly exist on the upper tidal flat, provide a natural barrier against sea level rise and coastal storm. The extremely shallow water stages (water depth< 0.2 m), including the initial stage of flood tides and the last stage of ebb tides, can induce a significant impact on sediment dynamics of saltmarshes and associated tidal flats, despite lasting for only a short time (around 10 min), which has been less studied. In this study, two parallel field sites were established to quantify erosion-accretion processes and morphological changes during extremely shallow water stages in salt marshes within Doulonggang tidal flat along the Jiangsu coast. Our results revealed that obvious accretion occurred during extremely shallow water stages, with a total deposition amount of +33.8 mm in vegetated areas and +20.8 mm in unvegetated areas. In contrast, erosion dominated during deep water stages, with a total erosion amount of -22.3 mm at the vegetated site and -32.7 mm at the unvegetated site. The magnitude of bed-level change during extremely shallow water stages was 7~8 times greater than that during deep water stages, even though the duration of extremely shallow water stages was only about 14~15% of the entire tidal cycle. Furthermore, strong winds significantly impacted deposition during extremely shallow water stages compared to calm weather. During the strong wind period, the average bed level change rate reached +0.15 mm/min and +0.12 mm/min in the vegetated and unvegetated areas, respectively. This is significantly higher than the +0.05 mm/min and +0.01 mm/min during the calm weather period. These results reveal that extremely shallow water stages have substantial impacts on sedimentary processes, which are vital for the maintenance of tidal flat systems.

First report of Fusarium foetens causing root rot on lavender (Lavandula angustifolia) in China - Xue-Jun Wei; Bing-Guo Jia; Xing Wang; Nan-Yang Li; Su-Na Wang; Li Li; Ai Zhang; Hao-Tian Zhang; Li-Ping Wang (Journal of Plant Pathology, 2023)

Corrigendum to “Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus)” [Aquaculture 563 (2023) /739023] - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Impacts of climate change on vicennial spatial behaviors of Trichiurus japonicus in the East China Sea - Yan Jin; Xing-Wei Yuan; Yi Zhang; Jian-sheng Li; Li-ping Yan; Zun-lei Liu; Jia-hua Cheng (Estuarine, Coastal and Shelf Science, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

The role of intercellular junction proteins in the penetration resistance of Drosophila larvae to avermectin - Li-Ping Chen; Han-Qing Jiang; Liang Luo; Jun Qiu; Xue-Jie Xing; Rui-Yan Hou; Yi-Jun Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Systematic toxicological analysis of the effect of salinity on the physiological stress induced by triphenyltin in Nile tilapia - Zhi-Hua Li; Shaoying Xing; Ping Li; Shuwen He; Zhihan Cao; Xu Wang; Xuqian Cao; Bin Liu; Hong You (Aquatic Toxicology, 2023)

Glucocorticoid and glycolysis inhibitors cooperatively abrogate acute graft-versus-host disease - Qi Wen; Zheng-Li Xu; Yu Wang; Meng Lv; Yang Song; Zhong-Shi Lyv; Tong Xing; Lan-Ping Xu; Xiao-Hui Zhang; Xiao-Jun Huang; Yuan Kong (Science China Life Sciences, 2023)

Distribution and physical–biological controls of dimethylsulfide in the western tropical Indian Ocean during winter monsoon - Shi-Mei Liang; Xing Zhai; Cheng-Xuan Li; Ming Xin; Ping Sun; Xuan-Li Liu; Lin Liu; Bao-Dong Wang (Frontiers in Marine Science, 2023)
New field observation on distribution, turnover, and sea–air flux of three dimethylated sulfur compounds (dimethylsulfide (DMS), dimethylsulfoniopropionate, and dimethylsulfoxide) in the western tropical Indian Ocean (WTIO; 4°N–10°S, 61°–65°E) were conducted under the major Global Change and Air–Sea Interaction Program during the 2021/2022 Northeast Monsoon (December 21, 2021 to January 11, 2022). Significantly high surface concentrations of DMS were identified in the region of the Seychelles–Chagos Thermocline Ridge (SCTR; 5°–10°S). This occurred because the shallow thermocline/nitracline and associated upwelling fueled biological production of DMS in the subsurface, which was brought to the surface through vertical mixing. The calculated sea–air DMS flux was also significantly strong in the SCTR region during the Northeast Monsoon owing to combination of high wind speed and high surface concentration of DMS. This finding is similar to results obtained previously during the Southwest Monsoon, suggesting that the SCTR region is an area of active DMS emission during both the Northeast Monsoon and the Southwest Monsoon. Microbial consumption was the dominant pathway of DMS removal, accounting for 74.4% of the total, whereas the processes of photolysis (17.7%) and ventilation (7.9%) were less important. Future work should be undertaken in the WTIO to establish how DMS emission is linked to aerosol properties and climate change.

Transcriptomic analysis provides new insights into the secondary follicle growth in spotted scat (Scatophagus argus) - Mou-Yan Jiang; Yi-Fan Zhou; Hao Liu; You-Xing Peng; Yuan-Qing Huang; Si-Ping Deng; Yang Huang; Gang Shi; Chun-Hua Zhu; Guang-Li Li; Dong-Neng Jiang (Frontiers in Marine Science, 2023)
Spotted scat ( Scatophagus argus ) is an important mariculture fish that is of great economic significance in East and Southeast Asia. To date, there are no studies on ovary development and regulation in S. argus . Herein, the ovary transcriptome profiles of S. argus at different stages were constructed, and the genes and pathways potentially involved in secondary follicle growth were identified. A total of 25,426 genes were detected by sequencing the mRNAs from the ovary libraries at stage III (n=3) and IV (n=3). Notably, 2950 and 716 genes were up-regulated and down-regulated in the stage IV ovary, respectively, compared to the stage III ovary. The differentially expressed genes (DEGs) were found to be mostly involved in regulating steroidogenesis, vitellogenesis, lipid metabolism, and meiosis. Up-regulation of steroid hormone synthesis pathway genes ( fshr , cyp17a1 , and foxl2 ) and insulin-like growth factor pathway genes ( igf1r , ifg2r , igfbp1 , igfbp3 , and igfbp7 ) in the ovary at stage IV was possibly the reason for the increased serum estrogen. Moreover, ppara , ppard , fabp3 , and lpl were up-regulated in the stage IV ovary and were potentially involved in the lipid droplet formation in the oocyte. Many DEGs were involved in the cellular cycle, meiosis, and cAMP or cGMP synthesis and hydrolysis, indicating that meiosis was restarted at stage IV ovary. In addition, numerous TGF-beta signal pathway genes were up-regulated in the stage IV ovary. This ovary transcript dataset forms a baseline for investigating functional genes associated with oogenesis in S. argus .

Evaluation of Fe3O4-MnO2@RGO magnetic nanocomposite as an effective persulfate activator and metal adsorbent in aqueous solution - Mang Lu; Xue-jiao Wu; Chu-xing Wan; Qiu-ping Gong; Jia-xin Li; Shuang-shuang Liao; Yu-an Wang; Shu-hao Yuan (Environmental Science and Pollution Research, 2023)

Assessing the ecotoxicity of combined exposure to triphenyltin and norfloxacin at environmental levels: A case study of immunotoxicity and metabolic regulation in carp (Cyprinus carpio) - Si-Qi Zhang; Ping Li; Shu-Wen He; Shao-Ying Xing; Zhi-Han Cao; Xue-Li Zhao; Cuici Sun; Zhi-Hua Li (Chemosphere, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Remediation of lindane contaminated soil by fluidization-like dielectric barrier discharge - Shuo Zhang; Zhen Liu; Shuran Li; Shihao Zhang; Hui Fu; Xuan Tu; Wenyi Xu; Xing Shen; Keping Yan; Ping Gan; Xiujuan Feng (Journal of Hazardous Materials, 2023)

Absence of water content contrast between lithosphere and asthenosphere in subduction zone - Yuto Sato; Eiichi Takahashi; Chang-Ming Xing; Li Li; Ze-Xian Cui; Wan-Feng Zhang; Xiao-Ping Xia (Earth and Planetary Science Letters, 2023)

Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus) - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Salt Bridge-intermediated three phase decoupling electrolytes for high voltage electrolytic aqueous Zinc-Manganese dioxides battery - Qi Xu; Qi-Xing Xie; Tong Xue; Gao Cheng; Jian-Dong Wu; Lan Ning; Xiang-Hui Yan; You-Jun Lu; Zhong-Li Zou; Bei-Ping Wang; Feng-Lan Han (Chemical Engineering Journal, 2023)

MdbHLH51 plays a positive role in anthocyanin accumulation in ‘Red Delicious’ apples - Gai-Xing Ning; Wen-Fang Li; Ming-Yu Chu; Zong-Huan Ma; Ping Wang; Juan Mao; Bai-Hong Chen (Trees, 2022)

An hourly shallow landslide warning model developed by combining automatic landslide spatial susceptibility and temporal rainfall threshold predictions - Yi-ming Cao; Wei Guo; Yu-ming Wu; Lang-ping Li; Yi-xing Zhang; Heng-xing Lan (Journal of Mountain Science, 2022)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

Depletion of serum-derived exosomes aggravates heat stress-induced damage of bovine mammary epithelial cells - Yue Wang; Hui-Li Wang; Zhi-Ping Lin; Ji-Feng Zhong; Kun-Lin Chen; Xing Duan (Molecular Biology Reports, 2022)

Evaluation of the microwave-assisted organic acid separation of organic sulfur from high-sulfur coal - Jin Liu; Chaoshun Jiang; Hao Shen; Zheng Pang; Zhi Wang; Ping Li; Xing Xing (Clean Technologies and Environmental Policy, 2022)

Belowground processes and sustainability in agroecosystems with intercropping - Rui-Peng Yu; Hao Yang; Yi Xing; Wei-Ping Zhang; Hans Lambers; Long Li (Plant and Soil, 2022)

Effects of long-term exposure of norfloxacin on the HPG and HPT axes in juvenile common carp - Si-Qi Zhang; Xue-Li Zhao; Shu-Wen He; Shao-Ying Xing; Zhi-Han Cao; Ping Li; Zhi-Hua Li (Environmental Science and Pollution Research, 2022)

A Mini-review of the Toxicity of Pollutants to Fish Under Different Salinities - Shao-Ying Xing; Zhi-Hua Li; Ping Li; Hong You (Bulletin of Environmental Contamination and Toxicology, 2022)

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

Antifungal sesquiterpenes with post-harvest anthracnose control effect on bananas from the fungus Fusarium lateritium - Junjie Zhu; Ping Xiong; Ziyang Li; Jiazhong Li; Longsheng Lin; Xing Fu; Yuxuan Huang; Yahong Xiong; Chunyuan Li (Natural Product Research, 2022)

Optimizing Method of Main Caverns in Large Underground Water-Sealed Storage Cavern - Yang An; E-Chuan Yan; Xing-Ming Li; Shao-Ping Huang (Geotechnical and Geological Engineering, 2022)

Optimization method of first-arrival waveform inversion based on the L-BFGS algorithm - Zhang Kai; Xu Xin; Liu Hong-Xing; Xu Yi-Peng; Li Zhen-Chun; Jiang Ping (Applied Geophysics, 2021)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Two new biflavanoids from Selaginella trichoclada Alsto - Yang Xie; Ping-Sheng Xu; Kang-Ping Xu; Zhen-Xing Zou; Gan Zhou; Dai Li; Dan Li; Xiao-Min Li; Jing Li; Gui-Shan Tan (Natural Product Research, 2021)

Migration and transformation of heavy metals in hyperaccumulators during the thermal treatment: a review - Wei Su; Xinyan Li; Hongshuo Zhang; Yi Xing; Ping Liu; Changqing Cai (Environmental Science and Pollution Research, 2021)

Methane Concentration in the Heartwood of Living Trees and Estimated Methane Emission on Stems in Upland Forests - Zhi-Ping Wang; Huan-Long Li; Hong-Hui Wu; Shi-Jie Han; Jian-Hui Huang; Xi-Mei Zhang; Xing-Guo Han (Ecosystems, 2021)

Investigation of the cumulative influence of infiltration on the slope stability with a thick unsaturated zone - Xiaokun Hou; Tonglu Li; Shengwen Qi; Songfeng Guo; Ping Li; Yu Xi; Xianli Xing (Bulletin of Engineering Geology and the Environment, 2021)

Ziziphus jujuba Mill., a plant used as medicinal food: a review of its phytochemistry, pharmacology, quality control and future research - Shi-Jun Liu; Yan-Ping Lv; Zhi-Shu Tang; Yu Zhang; Hong-Bo Xu; Dong-Bo Zhang; Chun-Li Cui; Hong-Bo Liu; Huan-Huan Sun; Zhong-Xing Song; Si-Min Wei (Phytochemistry Reviews, 2021)

LAI scale effect research based on compact airborne spectrographic imager data in the Heihe Oasis - Xiao-ai Dai; Chao Liu; Nai-wen Li; Mei-lian Wang; Yu-wei Yang; Xing-ping Yang; Shi-qi Zhang; Xu-wei He; Zheng-li Yang; Heng Lu; Jing-zhong Li; Ze-kun Wang (Journal of Mountain Science, 2021)

Exposed to Mercury-Induced Oxidative Stress, Changes of Intestinal Microflora, and Association between them in Mice - Yulan Zhao; Changming Zhou; Xiaoquan Guo; Guoliang Hu; Guyue Li; Yu Zhuang; Huabin Cao; Lin Li; Chonghong Xing; Caiying Zhang; Fan Yang; Ping Liu (Biological Trace Element Research, 2021)

Lithological and environmental controls on large tafoni along conglomerate cliffs in subtropic humid Danxiashan UNESCO Global Geopark - Xin Chen; Liu-qin Chen; Yan-hong Zhang; Ding-ding Du; Hai-ping Hu; Dong-xing Liu; Wen-zhuo Li (Journal of Mountain Science, 2021)

New cytotoxic biflavones from Selaginella doederleinii - Li-Fei Liu; Hui-Hui Sun; Jian-Bing Tan; Qi Huang; Fei Cheng; Kang-Ping Xu; Zhen-Xing Zou; Gui-Shan Tan (Natural Product Research, 2021)

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

2D slope stability analysis based on Pan’s maximum principle - Xiao Gang Wang; Xing Chao Lin; Ping Sun; Xu Li; Yu Jie Wang; Yong Yu Ling (Bulletin of Engineering Geology and the Environment, 2020)

Characterization of Pneumocystis jirovecii pneumonia at three tertiary comprehensive hospitals in southern China - Yan-Hui Chen; Xue-Yao Fang; Yue-Ting Li; Yan-Ling Liu; Ya-Ping Hang; Yan-Ping Xiao; Xing-Wei Cao; Qiao-Shi Zhong; Long-Hua Hu (Brazilian Journal of Microbiology, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Pectobacterium carotovorum subsp. brasiliensis and Pectobacterium parmentieri as causal agents of potato blackleg and soft rot in China - Wen Li-ping; Zhong Min; Ren Min-hua; Li Xing-wei; Liu Qiong-guang (Journal of Plant Pathology, 2020)

High throughput solid-phase screening of bacteria with cyclic amino alcohol deamination activity for enantioselective synthesis of chiral cyclic β-amino alcohols - Ya-Wen Chang; Jian-Dong Zhang; Xiao-Xiao Yang; Jing Li; Li-Li Gao; Shuang-Ping Huang; Xing-Mei Guo; Cao-Feng Zhang; Hong-Hong Chang; Jian-He Xu (Biotechnology Letters, 2020)

High-level soluble expression of human Cu,Zn superoxide dismutase with high activity in Escherichia coli - Jin-Ling Yang; Xing-Lun Li; Feng-Lin Jiang; Ting Gong; Jing-Jing Chen; Tian-Jiao Chen; Ping Zhu (World Journal of Microbiology and Biotechnology, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

NK cell reconstitution following unmanipulated HLA-mismatched/haploidentical transplantation compared with matched sibling transplantation - Li-Juan Hu; Xun-Hong Cao; Xing-Xing Yu; Xue-Fei Liu; Xiao-Su Zhao; Ying-Jun Chang; Xiao-Hui Zhang; Lan-Ping Xu; Yu Wang; Kai-Yan Liu; Xiao-Jun Huang; Xiang-Yu Zhao (Science China Life Sciences, 2020)

Microbial methane production is affected by secondary metabolites in the heartwood of living trees in upland forests - Huan-Long Li; Xi-Mei Zhang; Feng-Dan Deng; Xing-Guo Han; Chun-Wang Xiao; Shi-Jie Han; Zhi-Ping Wang (Trees, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Optimizing the frequency ratio method for landslide susceptibility assessment: A case study of the Caiyuan Basin in the southeast mountainous area of China - Yi-xing Zhang; Heng-xing Lan; Lang-ping Li; Yu-ming Wu; Jun-hui Chen; Nai-man Tian (Journal of Mountain Science, 2020)

Nocardia panacis sp. nov., a novel actinomycete with antiphytopathogen activity isolated from the rhizosphere of Panax notoginseng - Jia-Yun Hu; Lei Li; Guang Peng; Yi-Qing Li; Li-Hua Xu; Hui-Lin Guan; Li-Xing Zhao; Cui-Ping Miao (Antonie van Leeuwenhoek, 2020)

HprK Xcc is a serine kinase that regulates virulence in the Gram‐negative phytopathogen Xanthomonas campestris - Rui‐Fang Li; Ping Cui; Ping‐Zhen Wei; Xing‐Yan Liu; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2019)
Summary The HprK serine kinase is a component of the phosphoenolpyruvate phosphotransferase system (PTS) of bacteria that generally regulates catabolite repression through phosphorylation/dephosphorylation of the PTS protein PtsH at a conserved serine residue. However, many bacteria do not encode a complete PTS or even have an HprK homologue. Xanthomonas campestris pv. campestris ( Xcc ) is a pathogen that cause black rot disease in crucifer plants and one of the few Gram‐negative bacteria that encodes a homologue of HprK protein (herein HprK Xcc ). To gain insight into the role of HprK Xcc and other PTS‐related components in Xcc we individually mutated and phenotypically assessed the resulting strains. Deletion of hprK Xcc demonstrated its requirement for virulence and other diverse cellular processes associated including extracellular enzyme activity, extracellular‐polysaccharide production and cell motility. Global transcriptome analyses revealed the HprK Xcc had a broad regulatory role in Xcc . Additionally, through overexpression, double gene deletion and transcriptome analysis we demonstrated that hprK Xcc shares an epistatic relationship with ptsH . Furthermore, we demonstrate that HprK Xcc is a functional serine kinase, which has the ability to phosphorylate PtsH. Taken together, the data illustrates the previously unappreciated global regulatory role of HprK Xcc and previously uncharacterized PTS components that control virulence in this pathogen.

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Three new labdane-type diterpenoids from Callicarpa macrophylla Vahl. - Zhen-Hui Wang; Huan-Jun Xu; Yang-Yang Zhai; Lan-Ping Yang; Qiang Li; Mei Huang; Xing-Ying Chen; Wen-Kui Zhang; Yue-Li Meng; Qing-Ling Zhang; Chao Niu; Yan-Ru Zhang (Natural Product Research, 2019)

High-altitude and long-range transport of aerosols causing regional severe haze during extreme dust storms explains why afforestation does not prevent storms - Ping Guo; Shaocai Yu; Liqiang Wang; Pengfei Li; Zhen Li; Khalid Mehmood; Xue Chen; Weiping Liu; Yannian Zhu; Xing Yu; Kiran Alapaty; Eric Lichtfouse; et al. (Environmental Chemistry Letters, 2019)

Extreme stress threatened double rice production in Southern China during 1981–2010 - Sheng-Li Liu; Xing Wang; Shou-Tian Ma; Xin Zhao; Fu Chen; Xiao-Ping Xiao; Rattan Lal; Hai-Lin Zhang (Theoretical and Applied Climatology, 2019)

New adenine analogues and a pyrrole alkaloid from Selaginella delicatula - Cai-Ping Yao; Zhen-Xing Zou; Yan Zhang; Jing Li; Fei Cheng; Ping-Sheng Xu; Gan Zhou; Xiao-Min Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2019)

Characterization of Cucurbita maxima Fruit Metabolomic Profiling and Transcriptome to Reveal Fruit Quality and Ripening Gene Expression Patterns - He-Xun Huang; Ting Yu; Jun-Xing Li; Shu-Ping Qu; Man-Man Wang; Ting-Quan Wu; Yu-Juan Zhong (Journal of Plant Biology, 2019)

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

Digitizing and modeling of structural planes in fractured rock mass tunnel based on SfM - Shang-qu Sun; Li-ping Li; Cheng-shuai Qin; Hong-liang Liu; Yan-huan Zhang; Xing-zhi Ba (Arabian Journal of Geosciences, 2019)

The antitoxin MqsA homologue in Pseudomonas fluorescens 2P24 has a rewired regulatory circuit through evolution - Yong Wang; Si‐Ping Zhang; Meng‐Yuan Zhang; Megan L. Kempher; Ding‐Ding Guo; Jian‐Ting Han; Xuanyu Tao; Yi Wu; Li‐Qun Zhang; Yong‐Xing He (Environmental Microbiology, 2019)
Summary The mqsRA operon encodes a toxin–antitoxin pair that was characterized to participate in biofilm and persister cell formation in Escherichia coli . Notably, the antitoxin MqsA possesses a C‐terminal DNA‐binding domain that recognizes the [5’‐AACCT(N) 2‐4 AGGTT‐3′] motif and acts as a transcriptional regulator controlling multiple genes including the general stress response regulator RpoS. However, it is unknown how the transcriptional circuits of MqsA homologues have changed in bacteria over evolutionary time. Here, we found mqsA in Pseudomonas fluorescens ( PfmqsA ) is acquired through horizontal gene transfer and binds to a slightly different motif [5′‐TACCCT(N) 3 AGGGTA‐3′], which exists upstream of the PfmqsRA operon. Interestingly, an adjacent GntR‐type transcriptional regulator, which was termed AgtR, is under negative control of PfMqsA. It was further demonstrated that PfMqsA reduces production of biofilm components through AgtR, which directly regulates the pga and fap operons involved in the synthesis of extracellular polymeric substances. Moreover, through quantitative proteomics analysis, we showed AgtR is a highly pleiotropic regulator that influences up to 252 genes related to diverse processes including chemotaxis, oxidative phosphorylation and carbon and nitrogen metabolism. Taken together, our findings suggest the rewired regulatory circuit of PfMqsA influences diverse physiological aspects of P. fluorescens 2P24 via the newly characterized AgtR.

Crop diversity facilitates soil aggregation in relation to soil microbial community composition driven by intercropping - Xiu-li Tian; Cheng-bao Wang; Xing-guo Bao; Ping Wang; Xiao-fei Li; Si-cun Yang; Guo-chun Ding; Peter Christie; Long Li (Plant and Soil, 2019)

Effects of glyphosate on soybean metabolism in strains bred for glyphosate-resistance - Wei-yu Li; Ping Lu; Hao Xie; Gui-quan Li; Jing-xuan Wang; Dong-yu Guo; Xing-yu Liang (Physiology and Molecular Biology of Plants, 2019)

Challenges in predicting and simulating summer rainfall in the eastern China - Ping Liang; Zeng-Zhen Hu; Yunyun Liu; Xing Yuan; Xiaofan Li; Xingwen Jiang (Climate Dynamics, 2019)

Characterization and genome analysis of novel phage vB_EfaP_IME195 infecting Enterococcus faecalis - Ronghuan Wang; Shaozhen Xing; Feiyang Zhao; Ping Li; Zhiqiang Mi; Taoxing Shi; Hui Liu; Yigang Tong (Virus Genes, 2018)

Optimisation of extraction conditions for total saponins from Cynanchum wallichii using response surface methodology and its anti-tumour effects - Kun-jun Mao; Ping Huang; Li- Zhang; Hai-sheng Yu; Xing-zhuo Zhou; Xi-yong Ye (Natural Product Research, 2018)

Potential high-frequency off-target mutagenesis induced by CRISPR/Cas9 in Arabidopsis and its prevention - Qiang Zhang; Hui-Li Xing; Zhi-Ping Wang; Hai-Yan Zhang; Fang Yang; Xue-Chen Wang; Qi-Jun Chen (Plant Molecular Biology, 2018)

Hsp90 regulation affects the treatment of glucocorticoid for pancreatitis-induced lung injury - Yan Zhao; Ren-Ping Xiong; Xing Chen; Ping Li; Ya-Lei Ning; Nan Yang; Yan Peng; Yu-Lin Jiang; Yuan-Guo Zhou (Molecular and Cellular Biochemistry, 2018)

Phenolic constituents from Rheum nobile and their antioxidant activity - Ye Fei; Juan Wang; Bing Peng; Jiangnan Peng; Jing-Hong Hu; Zu-Ping Zeng; Jing Chen; Qi-En Li; Zeng-Ping Gao; Xing-Li Yan (Natural Product Research, 2017)

Cross-neutralization of SARS coronavirus-specific antibodies against bat SARS-like coronaviruses - Lei-Ping Zeng; Xing-Yi Ge; Cheng Peng; Wanbo Tai; Shibo Jiang; Lanying Du; Zheng-Li Shi (Science China Life Sciences, 2017)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Effect of Temperature–Water Coupled Actions on Joint Morphology - Jing-shuo Liu; Ping Cao; Jie Liu; Jin-xing Fan; Guo-guo Ning; Fu-liang Li (Geotechnical and Geological Engineering, 2017)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

Nuclear magnetic resonance T2 spectrum: multifractal characteristics and pore structure evaluation - Jian-Ping Yan; Xu He; Bin Geng; Qin-Hong Hu; Chun-Zhen Feng; Xiao-Pan Kou; Xing-Wen Li (Applied Geophysics, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

Koninginins R-S from the endophytic fungus Trichoderma koningiopsis - Ming Hu; Qi-Ling Li; Ya-Bin Yang; Kai Liu; Cui-Ping Miao; Li-Xing Zhao; Zhong-Tao Ding (Natural Product Research, 2017)

An UDP-Glucosyltransferase Gene from Barley Confers Disease Resistance to Fusarium Head Blight - Li-Ping Xing; Li-Qiang He; Jin Xiao; Qi-Guang Chen; Ming-Hao Li; Yi Shang; Yan-Fei Zhu; Pei-Du Chen; Ai-Zhong Cao; Xiu-E Wang (Plant Molecular Biology Reporter, 2017)

Genetic characterization of H9N2 avian influenza virus in plateau pikas in the Qinghai Lake region of China - Yan Yan; Jin-Yan Gu; Zhuang-Chuan Yuan; Xin-Yu Chen; Zeng-Kui Li; Jing Lei; Bo-li Hu; Li-Ping Yan; Gang Xing; Min Liao; Ji-Yong Zhou (Archives of Virology, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Acne-Like Subcutaneous Phaeohyphomycosis Caused by Cladosporium cladosporioides: A Rare Case Report and Review of Published Literatures - Ya Bin Zhou; Ping Chen; Ting Ting Sun; Xing Jia Wang; Dong Ming Li (Mycopathologia, 2016)

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats - Hao-Tian Li; Xing-Zhang Zhao; Xin-Ran Zhang; Gang Li; Zhi-Qiang Jia; Ping Sun; Ji-Quan Wang; Zhong-Kai Fan; Gang Lv (Molecular Neurobiology, 2016)

Inhibitory effect of Gardenblue blueberry (Vaccinium ashei Reade) anthocyanin extracts on lipopolysaccharide-stimulated inflammatory response in RAW 264.7 cells - Wei Xu; Qing Zhou; Yong Yao; Xing Li; Jiu-liang Zhang; Guan-hua Su; Ai-ping Deng (Journal of Zhejiang University-SCIENCE B, 2016)

Silver nanoparticles formation by extracellular polymeric substances (EPS) from electroactive bacteria - Shan-Wei Li; Xing Zhang; Guo-Ping Sheng (Environmental Science and Pollution Research, 2016)

Two new eunicellin diterpenoids from the South China Sea gorgonian Muricella sibogae and their bioactivities - Xing-Wang Zhang; Xu-Li Tang; Hong-Rui Yuan; Dan-Qing Feng; Pei Su; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2015)

Bacterial growth efficiency in a partly eutrophicated bay of South China Sea: Implication for anthropogenic impacts and potential hypoxia events - Xing-Yu Song; Hua-Xue Liu; Yu Zhong; Ye-Hui Tan; Geng Qin; Kai-Zhi Li; Ping-Ping Shen; Liang-Min Huang; You-Shao Wang (Ecotoxicology, 2015)

Anti-inflammatory effect of procyanidin B1 on LPS-treated THP1 cells via interaction with the TLR4–MD-2 heterodimer and p38 MAPK and NF-κB signaling - Jing Xing; Rui Li; Nan Li; Jian Zhang; Yueqing Li; Ping Gong; Dongna Gao; Hui Liu; Yu Zhang (Molecular and Cellular Biochemistry, 2015)

Generation and characterization of Brassica rapa ssp. pekinensis – B. oleracea var. capitata monosomic and disomic alien addition lines - AI XIA GU; SHU XING SHEN; YAN HUA WANG; JIAN JUN ZHAO; SHU XIN XUAN; XUE PING CHEN; XIAO FENG LI; SHUANG XIA LUO; YU JING ZHAO (Journal of Genetics, 2015)

Kinetic changes of regulatory B10 cells in collagen-induced arthritis could be regulated by cytokines IFN-γ and TGF-β1 - Zhaohui Zheng; Tao Liu; Xueyi Li; Jin Ding; Yuan Feng; Jinlin Miao; Xing Luo; Zhenbiao Wu; Ping Zhu (Inflammation Research, 2015)

Effects of delayed motherhood on hippocampal gene expression in offspring rats - Ping Duan; Bo Li; Caifang Li; Xuefei Han; Yan Xu; Ying Xing; Wenhai Yan (Molecular and Cellular Biochemistry, 2015)

Marker-assisted breeding for transgressive seed protein content in soybean [Glycine max (L.) Merr.] - Ying Hu Zhang; Mei Feng Liu; Jian Bo He; Yu Feng Wang; Guang Nan Xing; Yan Li; Shou Ping Yang; Tuan Jie Zhao; Jun Yi Gai (Theoretical and Applied Genetics, 2015)

Potent CDC25B and PTP1B phosphatase inhibitors: 2′,4′,6′-trihydroxylchalcone derivatives - Shui-Lian Zhao; Zhou Peng; Xing-Hua Zhen; Hong-Guo Jin; Yan Han; You-Le Qu; Li-Ping Guan (Medicinal Chemistry Research, 2015)

A Novel Oral Preparation of Hydroxysafflor Yellow A Base on a Chitosan Complex: A Strategy to Enhance the Oral Bioavailability - Guan-nan Ma; Fang-lin Yu; Shan Wang; Zhi-ping Li; Xiang-yang Xie; Xing-guo Mei (AAPS PharmSciTech, 2015)

Genetic polymorphisms of CYP2D6*10 and the effectiveness of combined tamoxifen citrate and testosterone undecanoate treatment in infertile men with idiopathic oligozoospermia - Kai-fa Tang; Yi-li Zhao; Shang-shu Ding; Qi-fei Wu; Xing-yang Wang; Jia-qi Shi; Fa Sun; Jun-ping Xing (Journal of Zhejiang University-SCIENCE B, 2015)

Brittleness index and seismic rock physics model for anisotropic tight-oil sandstone reservoirs - Xin-Rui Huang; Jian-Ping Huang; Zhen-Chun Li; Qin-Yong Yang; Qi-Xing Sun; Wei Cui (Applied Geophysics, 2015)

Urgent landslide susceptibility assessment in the 2013 Lushan earthquake-impacted area, Sichuan Province, China - Zhi-hua Yang; Heng-xing Lan; Xing Gao; Lang-ping Li; Yun-shan Meng; Yu-ming Wu (Natural Hazards, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Paleoclimate modeling in China: A review - Dabang Jiang; Ge Yu; Ping Zhao; Xing Chen; Jian Liu; Xiaodong Liu; Shaowu Wang; Zhongshi Zhang; Yongqiang Yu; Yuefeng Li; Liya Jin; Ying Xu; et al. (Advances in Atmospheric Sciences, 2015)

Post-earthquake rainfall-triggered slope stability analysis in the Lushan area - Zhi-hua Yang; Heng-xing Lan; Hong-jiang Liu; Lang-ping Li; Yu-ming Wu; Yun-shan Meng; Liang Xu (Journal of Mountain Science, 2015)

A new porcine reproductive and respiratory syndrome virus strain with highly conserved molecular characteristics in its parental and attenuated strains - Xing Liu; Yufeng Li; Qi Lu; Juan Bai; Xiaoye Wang; Ping Jiang (Virus Genes, 2014)

Lipid response to short-term chilling shock and long-term chill hardening in Jatropha curcas L. seedlings - Zhong-Guang Li; Hua-Zong Zeng; Ping-xing Ao; Ming Gong (Acta Physiologiae Plantarum, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Haplotype analysis of TLR4 gene and its effects on milk somatic cell score in Chinese commercial cattle - Xing Ping Wang; Zhuo Ma Luoreng; Shu Xin Gao; Dong Sheng Guo; Jun Ya Li; Xue Gao; Shang Zhong Xu; Feng Li; Gang Chen; Jin Ren Wang (Molecular Biology Reports, 2014)

Characteristics of gas disaster in the Huaibei coalfield and its control and development technologies - Liang Wang; Yuan-ping Cheng; Feng-hua An; Hong-xing Zhou; Sheng-li Kong; Wei Wang (Natural Hazards, 2014)

Three Novel SNPs in the Coding Region of the Bovine MC3R Gene and Their Associations with Growth Traits - Zhuo Ma Luoreng; Xing Ping Wang; Yun Ma; Feng Li; Dong Sheng Guo; Na Li; Jin Ren Wang (Biochemical Genetics, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Activation of BKCa Channels Mediates Hippocampal Neuronal Death After Reoxygenation and Reperfusion - Ming Chen; Hong-Yu Sun; Ping Hu; Chun-Fei Wang; Bo-Xing Li; Shu-Ji Li; Jian-Jun Li; Hui-Ying Tan; Tian-Ming Gao (Molecular Neurobiology, 2013)

Involvement of compatible solutes in chill hardening-induced chilling tolerance in Jatropha curcas seedlings - Ping-Xing Ao; Zhong-Guang Li; Ming Gong (Acta Physiologiae Plantarum, 2013)

Damage and Permeability Development in Coal During Unloading - Hai-Dong Chen; Cheng Yuan-Ping; Hong-Xing Zhou; Wei Li (Rock Mechanics and Rock Engineering, 2013)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

Dietary consumption and diet diversity and risk of developing bladder cancer: results from the South and East China case–control study - Fatima Isa; Li-Ping Xie; Zhiquan Hu; Zhaohui Zhong; Marjolein Hemelt; Raoul C. Reulen; Y. C. Wong; Po-Chor Tam; Kai Yang; Chao Chai; Xing Zeng; Yilan Deng; et al. (Cancer Causes & Control, 2013)

A new furolactone-type lignan from Lycium chinense - Xing-Nuo Li; Chu Chu; Sheng-Qiang Tong; Dong-Ping Cheng; Ji-Zhong Yan (Natural Product Research, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Involvement of antioxidant defense system in chill hardening-induced chilling tolerance in Jatropha curcas seedlings - Ping-Xing Ao; Zhong-Guang Li; Dong-Mei Fan; Ming Gong (Acta Physiologiae Plantarum, 2013)

Genetic polymorphisms of lipoprotein lipase gene and their associations with growth traits in Xiangxi cattle - Xing Ping Wang; Zhuo Ma Luoreng; Feng Li; Jin Ren Wang; Na Li; Shu Hong Li (Molecular Biology Reports, 2012)

Two phthalide dimers from the radix of Angelica sinensis - Xing-Nuo Li; Yuan-Yi Chen; Dong-Ping Cheng; Sheng-Qiang Tong; Hai-Bin Qu; Ji-Zhong Yan (Natural Product Research, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

The evolution and utility of ribosomal ITS sequences in Bambusinae and related species: divergence, pseudogenes, and implications for phylogeny - HUI-XING SONG; SU-PING GAO; MING-YAN JIANG; GUANG-LI LIU; XIAO-FANG YU; QI-BING CHEN (Journal of Genetics, 2012)

Response to weaning and dietary l-glutamine supplementation: metabolomic analysis in piglets by gas chromatography/mass spectrometry - Ying-ping Xiao; Tian-xing Wu; Qi-hua Hong; Jiang-ming Sun; An-guo Chen; Cai-mei Yang; Xiao-yan Li (Journal of Zhejiang University-SCIENCE B, 2012)

Highly Sensitive Detection of Residual Chlorpromazine Hydrochloride with Solid Substrate Room Temperature Phosphorimetry - Jia-Ming Liu; Li-ping Lin; Xin-Xing Wang; Xuan Lin; Ping Zhou; Shao-Qin Lin; Zhi-Yong Zheng (Journal of Fluorescence, 2012)

Identification of a new Bombyx mori nucleopolyhedrovirus and analysis of its bro gene family - Jing-Bo Zhou; Xing-Qi Li; Wanchai De-Eknamkul; Siripuk Suraporn; Jia-Ping Xu (Virus Genes, 2012)

Dysregulation of the β3 integrin-VEGFR2 complex in Hantaan virus–directed hyperpermeability upon treatment with VEGF - Wei Wang; Ye Zhang; Yu Li; Lei Pan; Lu Bai; Yan Zhuang; Chang-Xing Huang; Jiu-Ping Wang; Hai-Tao Yu; Xin Wei; Wei Jiang; Ya-Yun Nan; et al. (Archives of Virology, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Proteomic Analysis of Osmotic Stress-Responsive Proteins in Sugarcane Leaves - Gui Zhou; Li-Tao Yang; Yang-Rui Li; Cheng-Lin Zou; Li-Ping Huang; Li-Hang Qiu; Xing Huang; Manoj Kumar Srivastava (Plant Molecular Biology Reporter, 2012)

The different expression of immune-related cytokine genes in response to velogenic and lentogenic Newcastle disease viruses infection in chicken peripheral blood - Wen-Quan Liu; Ming-Xing Tian; Yuan-Ping Wang; Yang Zhao; Nian-Li Zou; Fang-Fang Zhao; San-Jie Cao; Xin-Tian Wen; Ping Liu; Yong Huang (Molecular Biology Reports, 2012)

A Promising CdSe@CdS-Quantum Dots-Cysteine for the Determination of Trace IgE by Solid Substrate Room Temperature Phosphorescence Immunoassay - Jia-Ming Liu; Li-ping Lin; Zhen-Bo Liu; Min-Lan Yang; Xin-xing Wang; Li-hong Zhang; Ma-lin Cui; Li Jiao (Journal of Fluorescence, 2012)

Overexpression of the trehalose-6-phosphate synthase gene OsTPS1 enhances abiotic stress tolerance in rice - Hao-Wen Li; Bai-Sheng Zang; Xing-Wang Deng; Xi-Ping Wang (Planta, 2011)

Interleukin-6, but Not Soluble Adhesion Molecules, Predicts a Subsequent Mortality from Cardiovascular Disease in Patients with Acute ST-Segment Elevation Myocardial Infarction - Zhen-Xing Fan; Qi Hua; Yin-Ping Li; Rong-Kun Liu; Zheng Yang (Cell Biochemistry and Biophysics, 2011)

Identification and expression analysis of two growth hormone receptors in zanzibar tilapia (Oreochromis hornorum) - Feng-Ying Gao; Mai-Xin Lu; Xing Ye; Zhang-Han Huang; Huan Wang; Hua-Ping Zhu; Li-Ping Yang (Fish Physiology and Biochemistry, 2011)

The investigation of the interaction between ribavirin and bovine serum albumin by spectroscopic methods - Xing-Jia Guo; Ai-Jun Hao; Xiao-Wei Han; Ping-Li Kang; Yu-Chun Jiang; Xiang-Jun Zhang (Molecular Biology Reports, 2011)

Profile of Organochlorine Pesticides in Soil Cores from Some Hotspot Areas of Beijing, China - Hang-Xin Cheng; Xing-Hong Li; Ya-Ping Wang; Chuan-Dong Zhao; Ying-Han Liu; Hong-Han Chen; Xiao-Bai Xu (Bulletin of Environmental Contamination and Toxicology, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Pseudonocardia bannaensis sp. nov., a novel actinomycete isolated from the surface-sterilized roots of Artemisia annua L. - Guo-Zhen Zhao; Jie Li; Wen-Yong Zhu; Xiu-Ping Li; Shou-Zheng Tian; Li-Xing Zhao; Li-Hua Xu; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Molecular characterisation of cereal cyst nematodes in winter wheat on the Huang-Huai floodplain of China using RFLP and rDNA-ITS sequence analyses - Bo Fu; Hong-xia Yuan; Yu Zhang; Xing-song Hou; Gao-lei Nian; Peng Zhang; Xiao-ping Xing; Bing-jian Sun; Ian T. Riley; Hong-lian Li (Australasian Plant Pathology, 2011)

Microarray analysis of the gene expression profile in the midgut of silkworm infected with cytoplasmic polyhedrosis virus - Ping Wu; Xiu Wang; Guang-xing Qin; Ting Liu; Yun-Feng Jiang; Mu-Wang Li; Xi-Jie Guo (Molecular Biology Reports, 2011)

Determination of Trace Deoxyribonucleic Acid by Using Fluorescein Isothiocyanate-Phenosafranine as a Double-Luminescent Phosphorescence Probe - Jia-Ming Liu; Xiao-Mei Huang; Zhen-Bo Liu; Fei-Ming Li; Li-Ping Lin; Xin-Xing Wang; Chang-Qing Lin; Ya-Hong Huang; Zhi-Ming Li; Shao-Qin Lin (Journal of Fluorescence, 2011)

Identification of molecular markers linked to the genes for purple grain color in wheat (Triticum aestivum) - Xing-Pu Li; Su-Que Lan; Ye-Lun Zhang; Yu-Ping Liu (Genetic Resources and Crop Evolution, 2010)

Remote chlorophyll- a retrieval in Case-II waters using an improved model and IRS-P6 satellite data - Jing-Ping Xu; Fang Li; Bai Zhang; Xing-Fa Gu; Tao Yu (International Journal of Remote Sensing, 2010)

Characterization of Five Putative Acyl Carrier Protein (ACP) Isoforms from Developing Seeds of Arachis hypogaea L. - Meng-Jun Li; Xing-Jun Wang; Lei Su; Yu-Ping Bi; Shu-Bo Wan (Plant Molecular Biology Reporter, 2010)

A new species of the genus Triplophysa (Nemacheilinae: Balitoridae), Triplophysa jianchuanensis sp. nov, from Yunnan, China - Lan-Ping Zheng; Li-Na Du; Xiao-Yong Chen; Jun-Xing Yang (Environmental Biology of Fishes, 2010)

A New Phosphorimetry for the Determination of Trace Alkaline Phosphatase Using Multi-wall Carbon Nanotubes and Its Diagnosis of Human Diseases - Jia-Ming Liu; Ying Rao; Li Chen; Xin-Xing Wang; Li-Ping Lin; Chang-Qing Lin; Li-Hong Zhang; Ying Ou-Yang (Journal of Fluorescence, 2010)

Sensitive Phosphorimetric Determination of Bumetanide in Human Urine with Its Inhibition Effect on the Formation of [Fe-morin] 3+ Complex - Li-Qing Zeng; Jia-Ming Liu; Fei-Ming Li; Xiao-Mei Huang; Li-Ping Lin; Xin-Xing Wang; Li-Hong Zhang; Chang-Qing Lin (Journal of Fluorescence, 2010)

Ubiquitin ligase Smurf1 targets TRAF family proteins for ubiquitination and degradation - Shan Li; Kefeng Lu; Jian Wang; Liguo An; Guiwen Yang; Hui Chen; Yu Cui; Xiushan Yin; Ping Xie; Guichun Xing; Fuchu He; Lingqiang Zhang (Molecular and Cellular Biochemistry, 2010)

Meiotic nondisjunction in resynthesized Brassica napus and generation of aneuploids through microspore culture and their characterization - Jing Wen; Xin-hua Zeng; Yuan-yuan Pu; Li-ping Qi; Zai-yun Li; Jin-xing Tu; Chao-zhi Ma; Jin-xiong Shen; Ting-dong Fu (Euphytica, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

New pathotypes of Heterodera avenae (cereal cyst nematode) from winter wheat in Zhengzhou, Henan, China - Hong-xia Yuan; Jun-wei Sun; Wei-xing Yang; Xiao-ping Xing; Zhen-yue Wang; Ian T. Riley; Hong-lian Li (Australasian Plant Pathology, 2010)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

A new species of Genus Triplophysa (Nemacheilinae: Balitoridae), Triplophysa longipectoralis sp. nov, from Guangxi, China - Lan-Ping Zheng; Li-Na Du; Xiao-Yong Chen; Jun-Xing Yang (Environmental Biology of Fishes, 2009)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

Distribution and Accumulation of Copper and Cadmium in Soil–Rice System as Affected by Soil Amendments - Ping Li; Xing-xiang Wang; Tao-lin Zhang; Dong-mei Zhou; Yuan-qiu He (Water, Air, & Soil Pollution, 2009)

Autophagy is activated and might protect neurons from degeneration after traumatic brain injury - Yan-Bo Zhang; Sheng-Xing Li; Xi-Ping Chen; Li Yang; Yun-Ge Zhang; Ran Liu; Lu-Yang Tao (Neuroscience Bulletin, 2008)

Solid lipid nanoparticles loading adefovir dipivoxil for antiviral therapy - Zhang Xing-guo; Miao Jing; Li Min-wei; Jiang Sai-ping; Hu Fu-qiang; Du Yong-zhong (Journal of Zhejiang University-SCIENCE B, 2008)

Successful tubes treatment of esophageal fistula - Ning Zhou; Wei-xing Chen; You-ming Li; Zhun Xiang; Ping Gao; Ying Fang (Journal of Zhejiang University-SCIENCE B, 2007)

Identification of poly-reactive natural IgM antibody that recognizes late apoptotic cells and promotes phagocytosis of the cells - Meng Fu; Ping-shen Fan; Wei Li; Cheng-xin Li; Ying Xing; Jing-gang An; Gang Wang; Xue-li Fan; Tian-wen Gao; Yu-feng Liu; Shigaku Ikeda (Apoptosis, 2007)

Research on the protection effect of pioglitazone for non-alcoholic fatty liver disease (NAFLD) in rats - Ping Xu; Xing-guo Zhang; You-ming Li; Chao-hui Yu; Lei Xu; Gen-yun Xu (Journal of Zhejiang University-SCIENCE B, 2006)

Nitrogen response efficiency increased monotonically with decreasing soil resource availability: a case study from a semiarid grassland in northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Shi-Ping Chen; Zheng-Wen Wang; Quan-Sheng Chen; Wen-Ming Bai (Oecologia, 2006)

Effects of different Rht-B1b, Rht-D1b and Rht-B1c dwarfing genes on agronomic characteristics in wheat - Xing-Pu Li; Su-Que Lan; Yu-Ping Liu; M. Gale; T. Worland (Cereal Research Communications, 2006)

Studies on the Interaction of Tricyclazole with β-cyclodextrin and human Serum Albumin by Spectroscopy - Hua-Xin Zhang; Xing Huang; Ping Mei; Ke-Hua Li; Cheng-Nong Yan (Journal of Fluorescence, 2006)

Study on energy transfer between carotenoid and chlorophyll a in cytochrome b 6 f complex from Bryopsis corticulans - Bin-Xing Li; Ping Zuo; Xiao-Bo Chen; Liang-Bi Li; Jian-Ping Zhang; Jian-Ping Zhang; Ting-Yun Kuang (Photosynthesis Research, 2006)

Cloning and Characterization of the First Cnidarian ADP-Ribosylation Factor, and Its Involvement in the Aiptasia-Symbiodinum Endosymbiosis - Ming-Chyuan Chen; Ying-Min Cheng; Li-Hsueh Wang; Chorng-Horng Lin; Xing-Yan Huang; Ming-Chin Liu; Ping-Jyun Sung; Lee-Shing Fang (Marine Biotechnology, 2004)